1991
DOI: 10.1136/gut.32.6.604
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical and manometric study comparing pneumatic dilatation and sublingual nifedipine in the treatment of oesophageal achalasia.

Abstract: The traditional approach to the treatment of patients with achalasia is based on stretching or cutting the muscle fibres at the oesophagogastric junction by pneumatic dilatation'6 or surgical myotomy.7 12 More recently, nitro derivatives and calcium antagonists, particularly nifedipine, have been proved to be effective in reducing lower oesophageal pressure and improving oesophageal emptying in patients with achalasia.' '7 The results obtained both with surgical or mechanical procedures, such as myotomy and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
5

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 23 publications
2
26
0
5
Order By: Relevance
“…Coccia et al [14] compared the clinical and manometric effects of sublingual nifedipine with pneumatic dilation in a randomized controlled trial, where excellent or good clinical results were observed in 75% of dilated patients and in 77% of patients treated with nifedipine. One patient could not tolerate nifedipine because of headache.…”
Section: Nifedipine Versus Pneumatic Dilationmentioning
confidence: 98%
See 1 more Smart Citation
“…Coccia et al [14] compared the clinical and manometric effects of sublingual nifedipine with pneumatic dilation in a randomized controlled trial, where excellent or good clinical results were observed in 75% of dilated patients and in 77% of patients treated with nifedipine. One patient could not tolerate nifedipine because of headache.…”
Section: Nifedipine Versus Pneumatic Dilationmentioning
confidence: 98%
“…First, patients of any age and both sexes underwent clinical, manometric, radiographic, and endoscopic evaluation to confirm primary achalasia and were randomly assigned to two or more treatment groups. Second, severity of symptoms was evaluated by a modified symptom score [14] consisting of the sum of the scores for dysphagia, regurgitation, and chest pain. Third, esophageal function was reevaluated at 1 year after therapy by esophageal manometry.…”
Section: Study Selection Criteriamentioning
confidence: 99%
“…The long-acting nitrates, such as isosorbide dinitrate (Isordil, Wyeth-Ayerst, Philadelphia, Pa., USA), are effective in decreasing LES pressure by 30-65% when administered sublingually or orally, symptoms improve in 53-87% of patients with achalasia [11]. A study that compared sublingual nifedipine to sublingual isosorbide dinitrate noted that both agents decreased LES pressure but the effect was slightly, but not significantly, better with nitrates (65%) compared with nifedipine (49%) [12].…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Among the various substances used in clinical practice to relax the LES [10], we used nifedipine and isosorbide dinitrate (ISD), the effectiveness of which in decreasing LES pressure and improving symptoms of achalasia has been demonstrated by various manometric and clinical studies [12, 13, 14, 15]. Although ISD is more effective and faster in relaxing LES than nifedipine, we used the latter as the drug of choice because it has the advantage of reducing the amplitude of esophageal pressure waves less, as observed in a previous manometric study [16].…”
Section: Methodsmentioning
confidence: 99%